The nonlocal by time problem for evolutionary singular equations of infinite order - Gorodetskii, V.V.; Verezhak, G.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
The correct solvability of a nonlocal by time multipoint problem for evolutionary equations with the Bessel operator of infinite order in generalized spaces of the type S and spaces of the type S′ that are spaces of generalized functions of infinite order of the type of ultra distributions is proved.